Tradycja rękopiśmienna polskich przekładów biblijnych od XIII do XVI wieku - Rajmund Pietkiewicz (Wrocławski Przegląd Teologiczny)
Biblical texts reached the Kingdom of Piast along with missionaries arriving at Polish territories since 966. The first Bibles in Latin were imported. The oldest traces of biblical translations into Polish date back to the 13th century (Kinga’s Psalter). We can assume that the translation of the four Gospels and probably the whole of the New Testament existed in the 14th century. Half way through the 15th century the translation of the whole of the Old Testament came to exist (Queen Zofia’s Bible). The Book of Psalms enjoyed the greatest popularity (e. g. Floriański Psalter or Puławski Psalter), as well as Gospels. Biblical texts were copied in different forms: fragments of books  (e. g. penitential psalms); individual books as a whole (e. g. Psalter); the whole of the New and Old Testament (usually in volumes, such as Queen Zofia’s Bible); in the form of liturgical books and prayer books taking advantage of biblical texts (e. g. Codex Aureus, breviary); as voices and quotations. Monastic manuscript writing workshops, for example in Kłodzko and Cracow, were important centers of production of books with biblical texts. It was the demand for liturgical purposes, private piousness, so-called wearing out of books, evolution of the language, and administration and education development, that were among the reasons for manuscripts with biblical texts production.